2015
DOI: 10.1101/lm.037440.114
|View full text |Cite
|
Sign up to set email alerts
|

Time–place learning over a lifetime: absence of memory loss in trained old mice

Abstract: Time -place learning (TPL) offers the possibility to study the functional interaction between cognition and the circadian system with aging. With TPL, animals link biological significant events with the location and the time of day. This whatwhere-when type of memory provides animals with an experience-based daily schedule. Mice were tested for TPL five times throughout their lifespan and showed (re)learning from below chance level at the age of 4, 7, 12, and 18 mo. In contrast, at the age of 22 mo these mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 105 publications
(129 reference statements)
3
8
0
1
Order By: Relevance
“…CD1 mice were not studied because (a) none of the CD1 mice mastered the 3-arm TPL task and (b) CD1 mice mastering the 2-arm TPL task did not use a circadian but instead an ordinal (non-circadian) strategy. Likewise aged C57Bl/6 mice are unable to master the 3-arm TPL task, unless they were trained in this task earlier in their life (Mulder et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CD1 mice were not studied because (a) none of the CD1 mice mastered the 3-arm TPL task and (b) CD1 mice mastering the 2-arm TPL task did not use a circadian but instead an ordinal (non-circadian) strategy. Likewise aged C57Bl/6 mice are unable to master the 3-arm TPL task, unless they were trained in this task earlier in their life (Mulder et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we investigated TPL for the first time in the context of aging (Mulder et al, 2015 ). We found that most untrained C57Bl/6 mice were unable to acquire TPL at middle-age (17 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se cree que esta diferencia en parámetros promueve diferencias en el tipo de estrategia de estimación temporal que describe mejor los resultados obtenidos (Crystal, 2009). Se ha encontrado que las tareas de TPL diario involucran timing circadiano (Mulder, Gerkema, & Van der Zee, 2013;Mulder, Reckman, Gerkema, & Van der Zee, 2015), mientras que en TPL intervalar se aducen mecanismos intervalares de estimación temporal (Crystal, 2009;García-Gallardo & Carpio, 2016;Thorpe et al, 2007;Thorpe, Petrovic, & Wilkie, 2002).…”
unclassified